2020
DOI: 10.1590/1413-812320202511.31442020
|View full text |Cite
|
Sign up to set email alerts
|

Saúde cardiovascular e validação do escore autorreferido no Brasil: uma análise da Pesquisa Nacional de Saúde

Abstract: Resumo O objetivo deste artigo é estimar a prevalência de saúde cardiovascular e a validade do escore autorreferido na população brasileira. Estudo transversal, metodológico, com 8.943 indivíduos adultos e dados laboratoriais da Pesquisa Nacional de Saúde 2013. Escores utilizados: comportamental (índice de massa corporal, tabagismo, dieta, atividade física, ideal se ≥ 3 fatores ideais), biológico (tabagismo, dislipidemia, hipertensão e diabetes, ideal se ≥ 3 fatores ideais) e saúde cardiovascular (todos os fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 26 publications
2
10
0
Order By: Relevance
“…Fourth, cardiovascular health was determined by self-reported data. Although a recent study showed that self-reported cardiovascular health may represent a reliable and valid alternative to measured cardiovascular health, this may increase the risk of measurement bias. Incorrect assessment of cardiovascular health might lead to an underestimation of the reported associations.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, cardiovascular health was determined by self-reported data. Although a recent study showed that self-reported cardiovascular health may represent a reliable and valid alternative to measured cardiovascular health, this may increase the risk of measurement bias. Incorrect assessment of cardiovascular health might lead to an underestimation of the reported associations.…”
Section: Discussionmentioning
confidence: 99%
“…Insufficient surveillance and public awareness of hypercholesterolemia in middle-aged adults may contribute to the lower concordance of the person-centered and measured hypercholesterolemia compared to hypertension and T2D 21 , 22 . So far, only one previous cross-sectional study conducted in 8,943 middle-aged Brazilians has compared person-centered and measured CVH 23 . In that study, the sensitivity and specificity of the person-centered CVH were 92.4 and 48.5%, compared to 93.6 and 72.1% in the current study.…”
Section: Discussionmentioning
confidence: 99%
“…However, self-reported data to assess CVH metrics has been used in other studies 20 )-( 22 and has a good correlation with biological measures. 23 Another limitation of this study involves the comparison between subgroups of sociodemographic variables that may not have sufficient number of individuals in some categories, such as race/skin color. As positive points of the study, we highlight (i) the fact that it was performed in a representative sample of the Brazilian adult population and (ii) presented updated data on the prevalence of CVH in Brazil.…”
Section: Discussionmentioning
confidence: 99%